It is necessary to sum the functional sequence F(t) by 'n', while at each step of summation it is necessary to take 'n' from another array n(t).

1 visualizzazione (ultimi 30 giorni)
It is necessary to sum the functional sequence F(t) by 'n', while at each step of summation it is necessary to take 'n' from another array n(t) I mean nD(t).
%% initial conditions
global d k0 h_bar ksi m E;
Ef = 2.77*10^3;
Kb = physconst('boltzmann'); % 1.38*10^(-23)
T = 0.12:0.24:6.4;
m = 9.1093837*10^(-31);
Tc = 1.2;
%t = T./Tc;
t = 0.1:0.1:2;
nD = floor(375./(2.*pi.*t.*1.2) - 0.5);
D = 10^(-8); % толщина пленки
ksi = 10^(-9);
%d = D/ksi;
d = 1000;
E = Ef/(pi*Kb*Tc);
h_bar = (1.0545726*10^(-34));
k0 = (ksi/h_bar)*sqrt(2.*m.*pi.*Kb.*Tc);
C_2 = 0;
for n = 0:49
C_2 = C_2 + (1/(2.*n+1)).*k0.*real(sqrt(3601+1i.*(2.*n+1))-((1+1i)./sqrt(2)).*sqrt(2.*n+1)); % константа
end
%% calculation
F = f_calc(t);
plot(t,F, '-r');
%% F(t)
function F = f_calc(t)
global d k0 h_bar ksi m;
F = 0;
for i = 1:20
n = nD(1,i);
F = F + 1/(2*n+1).*(k0.*real(((f_p1(n,t)-f_p2(n,t))./2))+(f_arg_2(n,t)-f_arg_1(n,t))./d);
end
F = -F;
%F = -(1/d).*F;
%F = F - C_2;
end
function p1 = f_p1(n,t)
p1 = ((1+1i)./sqrt(2)).*sqrt(t.*(2.*n+1));
end
function p2 = f_p2(n,t)
global E;
p2 = sqrt(3601+1i.*t.*(2.*n+1));
end
function n_lg = f_lg(n,t)
global d k0;
arg_of_lg = (1+exp(-1i*d*k0.*f_p1(n,t)))/(1+exp(-1i*d*k0.*f_p2(n,t)));
n_lg = log(abs(arg_of_lg));
end
function arg_1 = f_arg_1(n,t)
global d k0;
arg_1 = angle(1+exp(-1i*d*k0.*f_p1(n,t)));
end
function arg_2 = f_arg_2(n,t)
global d k0;
arg_2 = angle(1+exp(-1i*d*k0.*f_p2(n,t)));
end

Risposte (1)

Voss
Voss il 8 Gen 2023
Redefine the function f_calc to take nD as its second argument. (You could also make nD a global variable.) See below:
%% initial conditions
global d k0 h_bar ksi m E;
Ef = 2.77*10^3;
Kb = physconst('boltzmann'); % 1.38*10^(-23)
T = 0.12:0.24:6.4;
m = 9.1093837*10^(-31);
Tc = 1.2;
%t = T./Tc;
t = 0.1:0.1:2;
nD = floor(375./(2.*pi.*t.*1.2) - 0.5);
D = 10^(-8); % толщина пленки
ksi = 10^(-9);
%d = D/ksi;
d = 1000;
E = Ef/(pi*Kb*Tc);
h_bar = (1.0545726*10^(-34));
k0 = (ksi/h_bar)*sqrt(2.*m.*pi.*Kb.*Tc);
C_2 = 0;
for n = 0:49
C_2 = C_2 + (1/(2.*n+1)).*k0.*real(sqrt(3601+1i.*(2.*n+1))-((1+1i)./sqrt(2)).*sqrt(2.*n+1)); % константа
end
%% calculation
F = f_calc(t,nD);
plot(t,F, '-r');
%% F(t)
function F = f_calc(t,nD)
global d k0 h_bar ksi m;
F = 0;
for i = 1:20
n = nD(1,i);
F = F + 1/(2*n+1).*(k0.*real(((f_p1(n,t)-f_p2(n,t))./2))+(f_arg_2(n,t)-f_arg_1(n,t))./d);
end
F = -F;
%F = -(1/d).*F;
%F = F - C_2;
end
function p1 = f_p1(n,t)
p1 = ((1+1i)./sqrt(2)).*sqrt(t.*(2.*n+1));
end
function p2 = f_p2(n,t)
global E;
p2 = sqrt(3601+1i.*t.*(2.*n+1));
end
function n_lg = f_lg(n,t)
global d k0;
arg_of_lg = (1+exp(-1i*d*k0.*f_p1(n,t)))/(1+exp(-1i*d*k0.*f_p2(n,t)));
n_lg = log(abs(arg_of_lg));
end
function arg_1 = f_arg_1(n,t)
global d k0;
arg_1 = angle(1+exp(-1i*d*k0.*f_p1(n,t)));
end
function arg_2 = f_arg_2(n,t)
global d k0;
arg_2 = angle(1+exp(-1i*d*k0.*f_p2(n,t)));
end

Prodotti

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by